Psychosocial needs of adolescents and young adults with eczema: A secondary analysis of qualitative data to inform a behaviour change intervention. Issue 1 (26th August 2020) - Ghio, Daniela; Greenwell, Kate; Muller, Ingrid; Roberts, Amanda; McNiven, Abigail; Santer, Miriam
: Objectives: This study aimed to explore adolescents and young adults' experiences of symptoms related to their eczema in order to determine their psychosocial needs. Design: A secondary qualitative analysis of two data sources collected through semi‐structured interviews for two different projects, SKINS project and Eczema Care Online project. Methods: In total, there were 28 transcripts with adolescents and young adults with eczema having a mean age of 19.5 years available to analyse. Interview data were collected from face‐to‐face interviews that were recorded and transcribed. Inductive thematic analysis explored data about symptoms and organized according to psychosocial needs. Results: Adolescents and young adults with eczema experience both visible symptoms (such as flaky, dry, and inflamed skin) and invisible symptoms (such as itch, pain, exhaustion, and mental distress) that elicit different psychosocial needs. These psychosocial needs are to (i) be understood; (ii) be perceived as normal; and (iii) receive emotional support. Interviewees described a struggle between wanting their peers and family to understand but take their eczema seriously whilst not wanting to stand out and instead to be perceived as 'normal', which they would define as being perceived as other adolescents. This has implications on behaviours, such as seeking support, avoiding going out, hiding their skin, as well as emotional implications, such as social isolation and feeling anxious and low. Conclusions: Having a better understanding of young people's experiences and psychosocial needs will provide a framework on how best to support adolescents and young adults when managing symptoms related to eczema. Statement of contribution What is already known on this subject? Eczema has a high impact on children and is considered a burden by children and adults with eczema. However, it is unclear what impact eczema has on adolescents and young adults. Adolescents and young adults with chronic conditions are known to be vulnerable to negative psychosocial outcomes but psychosocial needs and how to best support this age group with eczema are unknown What does this add? Three psychosocial needs were developed from evaluating the impact of visible and invisible symptoms of eczema: The need to feel understood (mostly reflective of invisible symptoms such as itch and pain and visible symptoms such as scratching). The need to be perceived as 'normal': visible symptoms such as flaky, inflamed skin make them stand out in comparison with their peers and a need emerged to blend in. The need for emotional support: adolescents and young adults searched for this from their health care providers, from shared experiences and from online resources. Adolescents and young adults with eczema appear to feel ambivalent about wishing the impact of the condition to be acknowledged whilst wishing the condition to be invisible to others. This ambivalence had further impact on feeling self‐conscious, seeking support, and dealing with unsolicited advice.